Electronic structure and reactivity of tirapazamine as a radiosensitizer - Romero, José; Maihom, Thana; Limão-Vieira, Paulo; Probst, Michael (Journal of molecular modeling, 2021)
Tirapazamine (TP) has been shown to enhance the cytotoxic effects of ionizing radiation in hypoxic cells, thus making it a candidate for a radiosensitizer. This selective behavior is often directly linked to the abundance of O 2 . In this paper, we study the electronic properties of TP in vacuum, micro-hydrated from one up to three molecules of water and embedded in a continuum of water. We discuss electron affinities, charge distribution, and bond dissociation energies of TP, and find that these properties do not change significantly upon hydration. In agreement with its large electron affinity, and bond breaking triggered by electron attachment requires energies higher than 2.5 eV, ruling out the direct formation of bioactive TP radicals. Our results suggest, therefore, that the selective behavior of TP cannot be explained by a one-electron reduction from a neighboring O 2 molecule. Alternatively, we propose that TP’s hypoxic selectivity could be a consequence of O 2 scavenging hydrogen radicals.